Tracking The Source of Antimicrobial Production From House Fly (Musca domestica): Right-Wing of Fly Or Gut System? - A Mini-Review - Muhammad Asril; Ika Agus Rini; Indah Oktaviani; Mushaliyah Mushaliyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: The house fly (Musca domestica) is a vector of disease-causing bacteria because of its habit of perching and feeding on various substrates of pathogenic bacteria. His role as a disease carrier contradicts the hadith narrated by Bukhari, which is